Effect of actinomycin D isolated from the cultured broth of marine streptomyces spp. On cell division protein FtsZ - Phennapa Charoenwiwattanakij (2020)
© 2020, Chiang Mai University. All rights reserved. In the course of our investigation on antibacterial substances with FtsZ inhibitory effect, actinomycin D was isolated from the ethyl acetate extract of Streptomyces sp. LT3-17. The compound showed antibacterial activities. The MIC values of actinomycin D against Staphylococcus aureus ATCC 25923, Methicillin-resistant Staphylococcus aureus DMST 20654, Bacillus subtilis ATCC 6633, Escherichia coli ATCC 25922, and Pseudomonas aeruginosa ATCC 27853 were 3.13, 0.39, 0.10, 300.00, and 500.00 µg/mL, respectively. The morphology study of E. coli JW0093 treated with the compound showed inhibitory effect on cell elongation. The inhibition of FtsZ activity by actinomycin D was shown as the inhibition of GTPase activity with IC50 value, 20.06 µM. The polymerization of E. coli FtsZ protein (EcFtsZ) treated with 0.01 µM actinomycin D showed the degree of polymerization ratio was less than 1.0 indicating the inhibitory potential of actinomycin D on FtsZ polymerization. In silico study was performed to predict binding mode of actinomycin D into nucleotide binding pocket of the homology model of EcFtsZ protein. From the results of these experiments, the isolation and elucidation methods of actinomycin D as well as its novel mechanism as FtsZ inhibitors have been discovered.